Pengembangan Sistem Manajemen Inventori Berbasis Web untuk PT Ling Komputer Indonesia - Bambang Hermanto; Ardiansyah; Rizky Prabowo; Agung Wijaya (Jurnal Pepadun, 2023)
The development of information technology currently provides opportunities for every company to have business competitiveness so that companies are required to have an information system that is able to support management in increasing company productivity. PT. Ling Komputer Indonesia still uses conventional business processes, in archiving stock data and the retrieval process from suppliers, so it requires a long process that results in data accumulation which results in increased data recording errors to the loss of transaction data. Seeing these problems, designing an information system at PT. Ling Komputer Indonesia is the solution chosen for convenience in the process of recording stock of goods and the process of picking up from suppliers. The information system built using the Waterfall method is expected to be able to help PT. Ling Komputer Indonesia in managing data quickly and precisely. Development of the system using the PHP and MySQL. This inventory information system, obtained results for 10 employees of PT Ling Komputer Indonesia who answered agree with the existence of this system. using the system by 71%.